ответ:cos^2x-√3 *sinxcosx=0
cosx(cosx - √3sinx)=0
cosx=0 -> x=pi/2+pi*k
cosx-√3sinx=0 Делим на2
1/2cosx-√3/2sinx=0
sin(pi/6-x)=0 -> pi/6-x = pi*l -> x=pi/6 - pi*l
Пошаговое объяснение:
ответ: cos^2x-√3 *sinxcosx=0
Покрокове пояснення:
ответ:cos^2x-√3 *sinxcosx=0
cosx(cosx - √3sinx)=0
cosx=0 -> x=pi/2+pi*k
cosx-√3sinx=0 Делим на2
1/2cosx-√3/2sinx=0
sin(pi/6-x)=0 -> pi/6-x = pi*l -> x=pi/6 - pi*l
Пошаговое объяснение:
ответ: cos^2x-√3 *sinxcosx=0
Покрокове пояснення:
cosx(cosx - √3sinx)=0
cosx=0 -> x=pi/2+pi*k
cosx-√3sinx=0 Делим на2
1/2cosx-√3/2sinx=0
sin(pi/6-x)=0 -> pi/6-x = pi*l -> x=pi/6 - pi*l